2017
DOI: 10.1177/1045389x17733330
|View full text |Cite
|
Sign up to set email alerts
|

A review of charge methods for driving piezoelectric actuators

Abstract: Piezoelectric actuators are the most commonly used actuators in nanopositioning. They provide excellent operating bandwidth and precision. These actuators are normally driven by voltage amplifiers; however, the relationship of the applied voltage on the actuator and its position is nonlinear and complex due to phenomena such as hysteresis. This adversely influences actuator’s position control which is the core component of nanopositioning. However, the electrical charge applied on a piezoelectric actuator has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…To eliminate the error brought by this assumption, a larger damping is used to dissipate the energy which should be dissipated by the effect of hysteresis indeed. Like this, the acceptable displacements of the PSA also can be predicted by the simper Equation (2).…”
Section: Modeling Of Psamentioning
confidence: 85%
See 1 more Smart Citation
“…To eliminate the error brought by this assumption, a larger damping is used to dissipate the energy which should be dissipated by the effect of hysteresis indeed. Like this, the acceptable displacements of the PSA also can be predicted by the simper Equation (2).…”
Section: Modeling Of Psamentioning
confidence: 85%
“…Piezoelectric actuators have been widely used in the fields of precision positioners with high-strain materials, multilayer device designs, and mass fabrication processes for portable electronic devices, ultrasonic motors for micro-robotics, and smart structures [1][2][3][4][5]. In addition to using the inverse piezoelectric effect of intelligent material, many relevant applications are also designed based on the structural contact-impact characteristics such as piezoelectric stack actuator (PSA, made in Tokyo, Japan) during the droplet formation of a liquid micro-dispenser [6], new piezoelectric driving quadruped micro-robot [7], novel impact rotary motor [8], and vibration excitation system equipped with PSA [9].…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric actuators based on the inverse piezoelectric effect are widely used in aerospace, biomedical, mechanical manufacturing, and microelectronic engineering owing to their compact size, fast response, easy integration and high positioning accuracy (Bazghaleh et al, 2018; Bi et al, 2017; Park et al, 2018). The most commonly used piezoelectric materials for piezoelectric actuators are piezoelectric ceramics and piezoelectric composites.…”
Section: Introductionmentioning
confidence: 99%
“…Not only, they are prominent actuators of nanopositioning at the moment; but also, they are likely to maintain this status for several years (Moheimani, 2008). Position control of (unfixed point(s)/surface(s) of) the actuator is the key task in piezo-actuated nanopositioning (Bazghaleh et al, 2018). In this article, position stands for relative position of the actuator respect to its position at the beginning of operation.…”
Section: Introductionmentioning
confidence: 99%
“…The former position control approach (tuning the piezoelectric voltage) has a major drawback: the relationship between an actuator’s position and its piezoelectric voltage is nonlinear, complex and still under investigation (Ahmadpour et al, 2015; An et al, 2018; Bazghaleh et al, 2018). A pioneer work reported that such nonlinearities can cause up to 40% error in position control of piezoelectric actuators (Barrett and Quate, 1991).…”
Section: Introductionmentioning
confidence: 99%